Lesbian, Gay, Bisexual & Trans-Sexual: a Christian Ethics Perspective - Tanugraha, Yoas; Amtiran, Abdon A (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This research analyzes ethical-theological responses to LGBT issues in Protestant context through in-depth study of key Biblical texts and related literature. Using a qualitative approach combining hermeneutical and contextual analysis, this research explores: interpretation of Biblical texts about LGBT, formulation of Christian ethical principles, development of theological-ethical responses, and pastoral care models. Research findings show that Biblical texts consistently and firmly reject LGBT practices as deviation from creation order. The research identifies seven fundamental ethical principles that should underlie church response: principles of creation, holiness, love, redemption, community, human dignity, and pastoral care. In implementation, churches need to develop a "convicted humility" approach that combines strong theological conviction with pastoral humility, distinguishing between behavior rejection and individual acceptance. Effective pastoral care models require integration of theological understanding with pastoral sensitivity, creating safe spaces for dialogue and healing while maintaining biblical truth. This research provides significant contribution in helping churches develop balanced responses between doctrinal firmness and pastoral love in handling LGBT issues.